Inactivation of Listeria innocua and Salmonella spp. in traditional Italian Spianata Piccante: a comparative study of three formulations (Italian Journal of Food Safety, 2026)
A challenge test was conducted to evaluate the efficacy of three Spianata Piccante formulations (A: traditional; B: with a bacteriocin-producing starter culture; C: with added dextrose) in reducing experimentally inoculated Listeria innocua, used as a surrogate for Listeria monocytogenes, and Salmonella spp. The aim was to identify the formulation that best ensured pathogen inactivation in compliance with United States (US) export requirements. Traditional Italian salami are considered shelf-stable due to multiple hurdle technologies, including pH reduction, decreased water activity and competitive microflora. However, these hurdles are often insufficient to reduce foodborne pathogens, particularly L. monocytogenes and Salmonella spp., to the levels required by the Food Safety and Inspection Service (FSIS) regulations (≥3 log₁₀ CFU/g for L. monocytogenes and ≥5 log₁₀ CFU/g for Salmonella spp.). High-pressure processing (HPP), a non-thermal treatment capable of inactivating vegetative pathogens, can be applied to achieve these reductions. In this study, meat batter was inoculated prior to stuffing (6 log₁₀ CFU/g), and pathogen reductions were evaluated after ripening and HPP treatment. Significant differences in microbial inactivation were observed among formulations (p
Keywords: Spianata Piccante; Italian salami; Salmonella spp.; Listeria innocua; high-pressure processing